Growth, Biomass, and Yield Responses of Agricultural Crops to Water Deficit Stress: A Review - Anandharaj , B.; Murugan , R.; Kanimozhi , G.; Priyanka , D.; Munnaji , P.; Arun , V.P. (International Journal of Scientific Research in Biological Sciences, 2024)
Various environmental stresses influence crop plants, affecting their growth and development and ultimately decreasing their productivity. Drought is a particularly harmful abiotic stressor to plant growth and yield in agricultural production, which has an impact on global food security. Global climate change accompanied by drought stress gradually depletes agriculture and affects food security globally. In plants, a better understanding of the morpho-physiological and biochemical basis of changes in water stress resistance could be used to select or create new varieties of crops to obtain better productivity under water deficit conditions. Globally, millets are a major food crop that has an extensive economic influence on developing countries. By elucidating the complex interactions between crops and water stress, this review provides valuable insights for researchers, policymakers, and agricultural practitioners seeking to enhance crop resilience and mitigate the impacts of water scarcity on global food security.